Formação continuada para inclusão de alunos com transtorno do espectro autista: desafios e possibilidades - Munaretti, Andreza dos Santos (2023)
The necessary appreciation of the diversity present in the school context is fundamental to helping the development of all students, particularly those with autism spectrum disorder (ASD). And the promotion of Inclusive Education and the training of educators to implement inclusion in classroom routines have a decisive influence on this scenario. Therefore, this research aimed to understand the perceptions of teachers in the process of school inclusion of students with ASD and carried out continuing training for these teachers. It was a qualitative, exploratory-descriptive study, using participant observation techniques. Data collection involved questionnaires sent to elementary school teachers, focusing on inclusive practices for students with ASD. In addition, a continuing education program was implemented, including an extension course and collaborative consultancy, with the aim of providing theoretical and practical knowledge about ASD. In the collaborative consultancy stage, the research used a Self-Efficacy Scale for Teachers of Students with Autism to verify the teachers' self-assessment. The results were analyzed using the Textual Discourse Analysis (TDA) framework. The results show that teachers face a series of daily challenges in their educational practice and often express the need for training for all the professionals involved, with a common understanding of the relevance of knowledge about autism and its applications for Inclusive Education.